Analysis of the Positional Forward Solution of 2（3-RPS） Parallel-serial Robot Motion Mechanism - 李峰; 李伟; 梁辉 (Jixie chuandong)
The parallel-serial robot motion mechanism,compared to the single parallel mechanism,the working space can be largely increased and so as its deflexion capacity,there for,its application foreground is broad. A positional forward analysis solution of 2（3-RPS） parallel-serial robot motion mechanism is presented. Firstly,the position coordinates of spherical joints on the upper platform of 3-RPS parallel mechanism are derived based on its structural characteristics,and then,a set of equations are listed according to the fixed side value of motion platform of each parallel mechanism,using iterative transformation method,a 16 order equation with one unknown variable is gained. All its positional forward solutions can be precisely derived after the structure parameters of the parallel-serial mechanism are determined. At last,the numerical example is presented,and 32 positional forward solutions are gained at the specific structure parameters.